White smoke the election of a pope - Macdonald, Sarah; Volker, Daniela; Monblat Jeremy ([Australia : BBC Active, 2005)
The end of John Paul II's papacy set in motion the centuries-old process of electing a new Pope. Known as a conclave, cardinals from all over the world gathered in the Sistine Chapel to decide upon a successor in obsolute secrecy. The release of white smoke signalled that a decision had been reached. Cardinal Ratzinger became Pope Benedict XVI. This film provides the inside story on how the cardinals made their decision and what their choice means to the Catholic Church as a whole
Executive producer, Farah Durrani
DVD format
Keywords: Popes -- Election